Comparison of marginal adaptation of Class II cavities restored with bulk-fill and conventional composite resins using different universal bonding agent application strategies - Soodabeh Kimyai; Mahdi Rahbar; Atefeh Ebrahimi; Saeedeh Asdagh (Wolters Kluwer Medknow Publications, 2020)
Background: This in vitro study was conducted to compare the effect of universal bonding application strategy (i.e., self-etch and etch-and-rinse) on marginal adaptation of bulk-fill and conventional composite resins in Class II restorations. Materials and Methods: In this in vitro study sixty sound premolars extracted for orthodontic reasons were selected. The samples were allocated to four groups based on the universal bonding application strategy (self-etch and etch and rinse) and type of composite (bulk-fill and conventional). In each group, boxes were prepared with a depth of 4 mm on the mesial surfaces. Finally, the marginal adaptation of the samples was evaluated under a stereomicroscope. Two-way ANOVA was used to compare the marginal adaptation data in the study. Statistical significance was set at P < 0.05. Results: Considering the type of universal bonding application strategy, there was a statistically significant difference in marginal adaptation. Etch-and-rinse strategy showed better marginal adaptation compared to self-etch strategy (P < 0.001). However, there was no statistically significant difference in marginal adaptation between the two composite resins (P = 0.829). Furthermore, the interaction between the two factors (type of universal bonding application strategy and type of composite resin) was not statistically significant (P = 0.629). Conclusion: Etch-and-rinse bonding application strategy in both the bulk-fill and conventional composite resins exhibited better marginal adaptation compared to self-etch bonding application strategy. However, the difference of marginal adaptation between the two types of composite resins (bulk and conventional) was not significant.